2019
DOI: 10.1039/c9ay00009g
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determination of heroin, fentanyl and fentalogues using high-performance liquid chromatography with diode array and amperometric detection

Abstract: Over recent years there has been a progressive increase in the adulteration of common illicit street drugs, such as heroin and cocaine, with fentanyl and its derivatives (fentalogues) being the cause of over doses ending with fatal repercussions. Consequently, there is a need for the development of sensitive, selective and reliable analytical protocols for their separation and quantification. Herein, we report for the first time, a combination of high-performance liquid chromatography with a dual-diode array a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…LC‐MS/MS (Liquid Chromatography‐Mass Spectrometry/ Mass Spectrometry) has been utilized to detect 24 fentanyl derivatives and metabolites in whole blood in under 14 min screening time . In addition, a dual HPLC‐DAD (High‐Performance Liquid Chromatography Diode‐Array Detector) and HPLC‐AD (Amperometric Detection) protocol that uses screen‐printed graphite macroelectrodes for amperometric detection has been developed for the simultaneous detection of 1 , 2 c and ten fentalogues . Furthermore, low‐field (62 MHz) NMR spectroscopy has been used to differentiate 65 fentalogues in conjunction with quantum mechanical spin system analysis of spectra acquired at a frequency of 600 MHz to produce comparison spectra .…”
Section: Introductionmentioning
confidence: 99%
“…LC‐MS/MS (Liquid Chromatography‐Mass Spectrometry/ Mass Spectrometry) has been utilized to detect 24 fentanyl derivatives and metabolites in whole blood in under 14 min screening time . In addition, a dual HPLC‐DAD (High‐Performance Liquid Chromatography Diode‐Array Detector) and HPLC‐AD (Amperometric Detection) protocol that uses screen‐printed graphite macroelectrodes for amperometric detection has been developed for the simultaneous detection of 1 , 2 c and ten fentalogues . Furthermore, low‐field (62 MHz) NMR spectroscopy has been used to differentiate 65 fentalogues in conjunction with quantum mechanical spin system analysis of spectra acquired at a frequency of 600 MHz to produce comparison spectra .…”
Section: Introductionmentioning
confidence: 99%
“…This approach was successfully applied for simultaneous analysis of investigational drugs of abuse in seized street samples in the presence of common adulterants (e. g. caffeine, paracetamol and benzocaine) and co-formulated excipients (starch, lactose, etc.). [108] A summary (analyte, sample, type of working electrode, LOD, and analytical frequency) on applications of SPEs coupled to HPLC systems are overviewed in Table 3.…”
Section: Spes Coupled To Hplc Systemsmentioning
confidence: 99%
“…Sisco et al have reported a very sensitive direct analysis in real‐time mass spectrometry [DART‐MS, limit of detection = 0.08–0.35 ng] and ion mobility spectrometry [IMS, limit of detection = 1.0–10.0 ng] screening methods, but neither of these techniques facilitated efficient separation of the 18 analogs within the study . High performance liquid chromatography (HPLC) has been applied in a number of studies including one validated method, which has been developed and utilized to quantify ( 2b ) within bulk forensic samples of heroin . Hyphenated techniques (LC–MS, LC‐MS 2 and UPLC‐MS 2 ) have also been applied to detect fentalogs and their metabolites in blood, urine and wastewater .…”
Section: Introductionmentioning
confidence: 99%